1994
DOI: 10.1021/np50111a001
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Studies of Sesquiterpenes with a cis-Fused Decalin System, 4. Synthesis of (+)-5βH-Eudesma-3,11-diene, (-)-5βH-Eudesmane-4β,11-diol, and (+)-5βH-Eudesmane-4α,11-diol, and Structure Revision of a Natural Eudesmane-4,11-diol Isolated from Pluchea arguta

Abstract: The syntheses of (+ )-5 3H-eudesma-3,11 -diene [1], (-)-5 ß -eudesmane-4ß, 11-diol [2], and (+ )-5ß -1 5 -4 , 11-diol [15] were carried out by an unambiguous procedure starting from -santonin. The diene 1 was identical with a natural product which was isolated previously as a termite defense substance. Although structure 2 was recently proposed for a new eudesmane-1,4-diol [A] isolated from Pluchea arguta, synthetic 2 and its C-4 epimer, 15, were not identical with this natural eudesmane-4,11-diol when their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 9 publications
5
37
0
Order By: Relevance
“…The irradiation of H-1, caused a NOE enhancement on the signals of H-14, H-2pax. These data confirmed the trans-fused decalin system of the eudesmane skeleton (Ando et al, 1994), leding to the identification of compound 7 as the new eudesmane sesquiterpene lactone 1-a-acetoxyeudesma-3,7(11)-dien-8,12-olide and the overall analysis of 1D and 2D NMR data enabled complete and unequivocal 1 H and 13 C NMR chemical shifts assignments (Table 1). Previously, only two similar semisynthetic compounds have been reported, one that was acetylated (Zdero and Bohlmann, 1989) and the other derived from the germacranolide laurenobiolide (Haruhiko and Kenichi, 1976).…”
Section: Isolation and Identification Of Compounds From Female Hb Extsupporting
confidence: 58%
“…The irradiation of H-1, caused a NOE enhancement on the signals of H-14, H-2pax. These data confirmed the trans-fused decalin system of the eudesmane skeleton (Ando et al, 1994), leding to the identification of compound 7 as the new eudesmane sesquiterpene lactone 1-a-acetoxyeudesma-3,7(11)-dien-8,12-olide and the overall analysis of 1D and 2D NMR data enabled complete and unequivocal 1 H and 13 C NMR chemical shifts assignments (Table 1). Previously, only two similar semisynthetic compounds have been reported, one that was acetylated (Zdero and Bohlmann, 1989) and the other derived from the germacranolide laurenobiolide (Haruhiko and Kenichi, 1976).…”
Section: Isolation and Identification Of Compounds From Female Hb Extsupporting
confidence: 58%
“…Thus, the X-ray diffraction experiments of pterodondiol were performed (figure 2), which revealed that the 7-isopropyl moiety was axial-oriented, opposite to that in the literature. According to the literature [7,8,13], the signal of C-5 and C-7 at ca. 54^2 and ca.…”
Section: Resultsmentioning
confidence: 97%
“…Comparison with those of cryptomeridiol (1b), the upfield shift of C-15 of hedytriol (1) was observed, due to g-gauch effect of 1b-OH. In addition, 1 was oxidized with PCC in acetone to yield 2-ketone (1a) [5], and then 1a was reduced by WolfKhishner-Huang method to afford cryptomeridiol (1b) [6], whose 1 H NMR, 13 C NMR, EI-MS and [a ] D were identical to those of authentic sample (Scheme 1) [7,8]. Therefore, the structure of 1 was unambiguously determined as (2 )-7aH-eudesmane-1b,4a, 11-triol.…”
Section: Resultsmentioning
confidence: 99%
“…The fraction (138 mg) of column B eluted with 60 ± 65 % MeOH (the 1100 ± 2000 mL fraction) was then separated on Sephadex LH-20 (13 500 mm) eluted with MeOH, followed by purification with HPLC (Develosil ODS UG-5, 10 250 mm, eluent, 80 % MeOH; flow rate, 1.5 mL/ min) to afford austroinulin (1, 4.6 mg) in the 75 ± 85 mL fraction. The fraction (182 mg) of column B eluted with 50 % MeOH (the 75 ± 85 mL fraction) was further separated on Sephadex LH-20 (column C: 13 500 mm) eluted with MeOH to give cryptomeridiol (11) [3] (25.5 mg) in the 80 ± 90 mL fraction, and the fraction of column C eluted with 120 ± 130 mL was purified by HPLC (Develosil ODS UG-5, 10 250 mm, eluent, 80 % MeOH; flow rate, 1. : + 16.98 (c 1.35, MeOH)} in the 0 ± 40 mL fraction. The fraction (185 mg) of column D eluted with 50 ± 100 % EtOAc in hexane (the 1100 ± 1400 mL fraction) was subjected to separation by an ODS sep-pak cartridge (70 % MeOH), followed by purification of the 0 ± 40 mL fraction with HPLC (Develosil ODS UG-5, 10 250 mm, eluent, 65 % MeOH; flow rate, 1.5 mL/min) to yield 4¢-hydroxy-5,6,7,3¢,5¢-pentamethoxyflavone (5, t R 19 min) [6] (2.8 mg), 5,6,7,3¢,4¢,5¢-hexamethoxyflavone (6, t R 27 min) [7] (14.1 mg), nobiletin (7, t R 36 min) [8] (10.6 mg), 5¢-methoxynobiletin (8, t R 42 min) [8] (35.4 mg), and 5,6,7,8,5¢-pentamethoxy-3¢,4¢-methylenedioxyflavone (9, t R 54 min) [8] (5.3 mg), while the fraction (26 mg) of column D eluted with 25 % EtOAc in hexane (the 300 ± 500 mL fraction) was also subjected to separation by an ODS sep-pak cartridge (70 % MeOH), followed by purification of the 0 ± 40 mL fraction with HPLC (Develosil ODS UG-5, 10 250 mm, eluent, 65 % MeOH; flow rate, 1.5 mL/min) to give sakuranetin {10, t R 41 min; [a] D 25 : ±23.28 (c 1.20, MeOH)) [4], [9] (1.9 mg).…”
Section: Introductionmentioning
confidence: 99%